On Approximation Properties of Stancu Type Post-Widder Operators Preserving Exponential Functions - TORUN, Gülten (Gazi University, 2022)
In this article, Stancu type Post-Widder operators are introduced, which are a modification of the Post-Widder operators that preserve the functions constant and e^2ax for fixed a>0. The uniform convergence of these modified operators for the function f on [0,∞) is examined and then the convergence rate is investigated with the help of the continuity module. The Voronovskaja type asymptotic formula is obtained to examine the asymptotic behavior of these operators. Finally, numerical examples and graphs are given to show the convergence of Stancu type Post- Widder operators and compared with Post Widder operators.
Keywords: Post-Widder Operators; Stancu Type Post-Widder Pperators; Modulus of Continuity; Voronovskaja Type Theorem